Falaise, as marcas da história numa cidade da Normandia - Confins (Confins)
The history of Falaise, a Normandy town, has been marked by two key historical events: the construction of William the Conqueror’s castle, and the battle of the “Falaise pocket”, the cause of major destruction at the end of the Second World War. These two events can still be seen in the urban landscape, particularly during the medieval festivals held every year around the castle, which still dominates the town, and at the memorial built to keep alive the memory of the population’s suffering.